Radiation exposure to dwellers due to naturally occurring radionuclides found in selected commercial building materials sold in Nigeria - Maxwell, O.; Adewoyin, O.O.; Joel, E.S.; Ehi-Eromesele, C.O.; Akinwumi, S.A.; Usikalu, M.R.; Emeike, C.P.; Embong, Z.; Hassaina, M. (ScienceDirect, 2018)
The activity concentration of 226Ra, 232Th and 40 K was measured in commonly building materials used in Nigeria from commercial supplier using High Purity Germanium Gamma (HPGe) detector. The mean activity concentrations in the samples were found to be 51.5 ± 9.3, 72.46 ± 17.65 and 217.05 ± 44.31 Bqkg-1 for 226Ra, 232Th and 40 K respectively. The highest radium equivalent (Raeq) of 273.9 Bqkg-1 was noted in Perfect Superfix White Cement (Nigeria) but found to be < 370 Bqkg-1 as the recommended dose limiting safe value for bulk media as presumed, the highest value of internal hazard index (Hin) and external hazard index (Hex) of 0.894 and 0.744 respectively were also < 1. The absorbed dose rate (DR) with a value of 122.52 nGyh-1 noted in ceramic tile sample is higher than the weighted population world average value of 80 nGyh-1 by a factor of 1.53. The highest annual effective dose rate (AEDR) of 0.601 mSvy-1 reported in PNT ceramics but was found to be less < 1 mSvy-1 . The investigated materials have the values of Hin, Hex and AEDR greater than 0.5 but less than1, showing that the dose impact exceeds the exemption dose level of 0.3 mSvy-1 for AEDR but complies to the upper limit of dose principle of 1 mSvy-1 .